O grupo escolar Gomes Cardim na perspectiva histórica do Espírito Santo nos anos iniciais da República: uma instituição escolar entre edificações (1908-1926) - Assis, Elezeare Lima de (2014)
Public elementary education, arranged in the format of grupo escolar, whose model was the generator of the first public elementary school in Vitória, Public School Gomes Cardin, is the object of this research. Our attention goes to the object in search of meanings which will allow us to understand the paths and difficulties of school, as well as the place this kind of school took in the actions of the government and in the context of the city during the period of time from Cardin Reform (1908) including the inauguration of the school in the same year and the moving of the school to another building in 1926. Period which was taken as a time cut, and as basis for the assessment of the sources. For the proceedings of the documentary analysis, we were guided by presuppositions of cultural history, in the perspectives, among others, of the concepts of strategy and tactic, the conceptions of reality in history from Michel de Certeau’s reflections. As we work with relations of power, and, consequently, of force, the propositions of Ginzburg matter to us, from history in fragments, in the composition of the whole, impregnated and expressed in signs, left where power “silences” and produces silences, which, when focused, reveal fragile voices, but producers of possibilities of news approaches, new readings of history.